Productivity and profitability enhancement in rice through precision N supply in north-eastern region of India - DEVI, A. DOLLINA; DASS, ANCHAL; DHAR, SHIVA; LAYEK, JAYANTA; SINGH, ARJUN; KAUR, RAMANJIT; SINGH, TEEKAM; NITHINKUMAR, KADAGONDA (Journal of Soil and Water Conservation, 2025)
Precision nitrogen (N) management is based on the demand of the crop and supplying capacity of the soil. Rice output in India is lagging behind as compared to other countries and nevertheless population growth has outplaced it. Rice being the most significant cereal crop in the NEH region of India, a field experiment was conducted in the region to analyze the effect of precision N management on productivity and profitability of rice in the year 2022. The treatment consisted of control (no-N), recommended dose of N (RDN) [80kg ha-1], soil-test crop response (STCR) based N (95 kg ha-1), 30% RDN Basal + SPAD meter ≤ 35 based N (64 kg ha-1), 30% RDN Basal + SPAD meter ≤ 37 based N (64 kg N ha-1), 30% RDN Basal + LCC < 4 (64 kg ha-1), 75% RDN + 2 nano-urea (NU) sprays, 50% RDN + NU. The results indicated that highest grain yield (4.84 t ha-1), net returns (INR 62120 ha-1) and B: C ratio (2.28) were achieved under STCR-based nitrogen management which was at par with SPAD meter ≤ 37 based N. There was saving of 16-31 kg N ha-1 in SPAD based N application without yield penalty compared to and STCR. Hence, N application could be scheduled using SPAD ≤ 37 as threshold value to increase the productivity and profitability of rice.